2018
DOI: 10.1103/physrevlett.121.027601
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Origin of Enhancement of Ferroelectricity in SnTe Ultrathin Films

Abstract: Previous studies showed that, as ferroelectric films become thinner, their Curie temperature (T_{c}) and polarization below T_{c} both typically decrease. In contrast, a recent experiment [Chang et al., Science 353, 274 (2016)SCIEAS0036-807510.1126/science.aad8609] observed that atomic-thick SnTe films have a higher T_{c} than their bulk counterpart, which was attributed to extrinsic effects. We find, using first-principles calculations, that the 0-K energy barrier for the polarization switching (which is a qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 50 publications
6
67
2
1
Order By: Relevance
“…Band bending is larger on a ferroelectrically-coupled (AA) 4 AL SnTe film when compared to an antiferroelectrically-coupled (AB ) 4 AL SnTe film, because the electric field lines cancel out at the exposed edge on the latter case. 70,71 Here, we use energetics and the experimental values of ∆α for 2 AL and 4 ALs, to demonstrate an antiferroelectric coupling on 4 AL SnTe that is at odds with previous claims of ferroelectric coupling 68,89 and consistent with experiment. 70,71 In the present calculations, the AA structure shown in Fig.…”
Section: Antiferroelectrically-coupled 4 Al Snte Filmsmentioning
confidence: 71%
See 2 more Smart Citations
“…Band bending is larger on a ferroelectrically-coupled (AA) 4 AL SnTe film when compared to an antiferroelectrically-coupled (AB ) 4 AL SnTe film, because the electric field lines cancel out at the exposed edge on the latter case. 70,71 Here, we use energetics and the experimental values of ∆α for 2 AL and 4 ALs, to demonstrate an antiferroelectric coupling on 4 AL SnTe that is at odds with previous claims of ferroelectric coupling 68,89 and consistent with experiment. 70,71 In the present calculations, the AA structure shown in Fig.…”
Section: Antiferroelectrically-coupled 4 Al Snte Filmsmentioning
confidence: 71%
“…These SnTe slabs have not been created by capping a bulk sample, but grown from the bottom up [70][71][72] . And while common theoretical approaches assume a slab can be obtained by cutting two opposing surfaces of bulk rocksalt 73 or rhombic 59,68,89 bulk samples, the present work is aimed to explore the structural evolution of a freestanding SnTe slab containing 2n ALs by the successive addition of a 2 ALs in the overall lowest-energy conformation to the slab containing 2(n−1) ALs with n a positive integer, complementing the experimental results of Ref. 71.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tensile strain can effectively enhance the Tc value while out‐of‐plane electric field can decrease the coercive field for the reversal of polarization. Liu et al explored intrinsic origin of enhancement of ferroelectricity in SnTe ultrathin films by first‐principles calculations and effective Hamiltonian simulations . They revealed that the FE switching energy barrier and Tc in freestanding, defect‐free SnTe thin films first increase with thickness when the film thickness is less than 5 UC, then decreases with thickness for thicker films.…”
Section: Exploration Of Low‐dimensional Ferroelectric Materialsmentioning
confidence: 99%
“…Different kinds of effective Hamiltonians were proposed to deal with different degrees of freedom [9][10][11][12][13]. In this work, we focus on the effective spin Hamiltonians of magnetic systems to illustrate the power of our method.…”
Section: Introductionsmentioning
confidence: 99%